The Merits of Mannitol in the Repair of Orbital Blowout Fracture - Shin, Kyung Jin; Lee, Dong Geun; Park, Hyun Min; Choi, Mi Young; Bae, Jin Ho; Lee, Eui Tae (Archives of Plastic Surgery, 2013)
Background One of the main concerns in orbital blowout fracture repair is a narrow operation field, due mainly to the innate complex three dimensions of the orbit; however, a deep location and extensive area of the fracture and soft tissue edema can also cause concern. Swelling of the orbital contents progresses as the operation continues. Mannitol has been used empirically in glaucoma, cerebral hemorrhage, and orbital compartment syndrome for decompression. The authors adopted mannitol for the control of intraorbital edema and pressure in orbital blowout fracture repair.Methods This prospective study included 108 consecutive patients who were treated for a pure blowout fracture from January 2007 to October 2012. For group I, mannitol was administered during the operation. Under general anesthesia, all patients underwent surgery by open reduction and insertion of an absorbable mesh implant. The authors compared postoperative complications, the reoperation rate, operation time, and surgical field improvement between the two groups.Results In patients who received intraoperative administration of mannitol, the reoperation rate and operation time were decreased; however, the difference was not statistically significant. The total postoperative complication rates did not differ. Panel assessment for the intraoperative surgical field video recordings showed significantly improved vision in group I.Conclusions For six years, mannitol proved itself an effective, reliable, and safe adjunctive drug in the repair of orbital blowout fractures. With its rapid onset and short duration of action, mannitol could be one of the best methods for obtaining a wider surgical field in blowout fracture defects.
Keywords: Orbital fractures; Mannitol; Intraoperative complication